Communication Problems Between Teacher and Students In English Subject - Wahidah Wahidah; Hayatul Ridha (Smart Education, 2020)
Abstract: This study was carried out to know the main factors that caused students' and teachers' communication problems in communicating using the English language in learning English subjects. The method used in this study is a qualitative approach with a descriptive design. This study's subjects were 26 students in the class VIII-3 of MTs Swasta MIM Langsa and the English teacher who taught at this class. The data were collected using three collecting data techniques; there were interviews, questionnaires, and observation. Based on the data collection, the researcher found that the main factors that caused students' communication problems in communicating by using the English language were semantical, grammatical, and phonological factors. It happened in the process of delivering information or receiving information. Other factors were the noise from outside of the classroom, vehicle sound, and the distance between the speaker and listener. The last factors that caused communication problems were students' psychology as a listener, such as weak memory and lack of motivation. The teacher also had communication problems, but it was caused by environmental factors (physical barriers). The teacher did the teacher ways to solve these obstacles, so that communication between students and teacher runs by using English. Keywords: communication; students; teachers Abstrak: Penelitian ini dilakukan untuk mengetahui faktor utama penyebab masalah komunikasi siswa dan guru dalam berkomunikasi menggunakan bahasa Inggris dalam pembelajaran mata pelajaran bahasa Inggris. Metode yang digunakan dalam penelitian ini adalah pendekatan kualitatif dengan desain deskriptif. Subjek penelitian ini adalah 26 siswa kelas VIII-3 MTs Swasta MIM Langsa dan guru bahasa Inggris yang mengajar di kelas ini. Pengumpulan data dilakukan dengan tiga teknik pengumpulan data; ada wawancara, kuesioner, dan observasi. Berdasarkan pengumpulan data, peneliti menemukan bahwa faktor utama yang menyebabkan masalah komunikasi siswa dalam berkomunikasi dengan menggunakan bahasa Inggris adalah faktor semantik, gramatikal, dan fonologis. Itu terjadi dalam proses menyampaikan informasi atau menerima informasi. Faktor lainnya adalah kebisingan dari luar kelas, suara kendaraan, dan jarak antara pembicara dan pendengar. Faktor terakhir yang menyebabkan masalah komunikasi adalah psikologi siswa sebagai pendengar, seperti daya ingat yang lemah dan motivasi yang kurang. Guru juga mengalami masalah komunikasi, namun disebabkan oleh faktor lingkungan (hambatan fisik). Guru melakukan cara-cara guru untuk mengatasi kendala tersebut, sehingga komunikasi antara siswa dan guru berjalan dengan menggunakan bahasa Inggris. Kata kunci: guru; komunikasi; siswa